2017
DOI: 10.1016/j.resuscitation.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Compression-to-ventilation ratio and incidence of rearrest—A secondary analysis of the ROC CCC trial

Abstract: Background Previous work has demonstrated that when out-of-hospital cardiac arrest (OHCA) patients achieve return of spontaneous circulation (ROSC), but subsequently have another cardiac arrest prior to hospital arrival (rearrest), the probability of survival to hospital discharge is significantly decreased. Additionally, few modifiable factors for rearrest are known. We sought to examine the association between rearrest and compression-to-ventilation ratio during cardiopulmonary resuscitation (CPR) and to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lastly, in the present study rearrest was once again found to be a strong predictor of poor resuscitation outcomes, including survival to hospital discharge and neurologic function, confirming recent findings from the ROC Continuous Chest Compressions trial. 6,26 In the prior study, no association was found between definitively classified compression-to-ventilation ratio and rearrest occurrence, an association that we had hypothesized was rooted in additional no-flow time created by regular cessation of chest compressions for delivery of ventilations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Lastly, in the present study rearrest was once again found to be a strong predictor of poor resuscitation outcomes, including survival to hospital discharge and neurologic function, confirming recent findings from the ROC Continuous Chest Compressions trial. 6,26 In the prior study, no association was found between definitively classified compression-to-ventilation ratio and rearrest occurrence, an association that we had hypothesized was rooted in additional no-flow time created by regular cessation of chest compressions for delivery of ventilations.…”
Section: Discussionmentioning
confidence: 81%
“…1 In this sense, antiarrhythmic administration can be contextualized to the intermediate resuscitation outcome of rearrest , including the rhythm-specific subcategory of recurrent VF, previously associated with poor survival to hospital discharge and/or neurologic outcomes by our group and others. 26 The mechanism of antiarrhythmics in obviating recurrent VF or rearrest during resuscitation is conceptually complicated by the known effect of some antiarrhythmic drugs to increase the defibrillation threshold, an effect that should reduce the probability of successful defibrillation. 79 Even so, it was demonstrated almost two decades ago that both amiodarone and lidocaine can improve survival to hospital admission when administered for recurrent or refractory VF.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous chest compression CPR (CCC-CPR) is one of the protocols that has been suggested as an alternative method to conventional CPR, with emphasis on immediate chest compression and delayed respiratory ventilation (6). In the 2010 European Resuscitation Council Guideline, CCC-CPR is recommended as an alternative method to conventional resuscitation.…”
Section: Introductionmentioning
confidence: 99%